Epidemiology and costs of severe acute respiratory infection and influenza hospitalizations in adults with diabetes in India - Parvaiz A Koul; Amit Bhavsar; Hyder Mir; Mark Simmerman; Hemant Khanna (Journal of Infection in Developing Countries)
Introduction: The incidence of diabetes mellitus is increasing rapidly in India. In addition to well-known complications, diabetes increases the risk for hospitalization and death from severe acute respiratory infection (SARI) and influenza. Here we examined the impact of SARI and influenza in Indian adults with diabetes.